Select all of the expressions that are equivalent to:

A.) (3x² - y)²

B.) (3x²)² - (y)²

C.) 9(x²)² - (y)²

D.) (9x²)² - (y)²

E.) (3x² + y)(3x² - y)

B.) (3x²)² - (y)²

C.) 9(x²)² - (y)²

D.) (9x²)² - (y)²

E.) (3x² + y)(3x² - y)

**Just evaluate each answer choice to see if it is a match.**

A.) (3x² - y)² → (3x² - y)(3x² - y) → 9x^4 - 6x²y + y² {used foil method}

B.) (3x²)² - (y)² → 9x^4 - y² {evaluated exponents}

C.) 9(x²)² - (y)² → 9x^4 - y² {evaluated exponents}

D.) (9x²)² - (y)² → 81x^4 - y² {evaluated exponents}

E.) (3x² + y)(3x² - y) → 9x^4 - y² {used foil method}

**B.) , C.) , and E.)**

**- Algebra House**